Norms, prices, and commitment: A comprehensive overview of field experiments in the energy domain and treatment effect moderators - Vesely, Stepan; Klöckner, Christian A.; Carrus, Giuseppe; Tiberio, Lorenza; Caffaro, Federica; Biresselioglu, Mehmet Efe; Kollmann, Andrea C.; Sinea, Anca C. (Frontiers in Psychology, 2022)
This paper provides a comprehensive overview of field experiments utilizing social norms, commitment and price-based interventions to promote energy conservation, load shifting, and energy efficiency behaviors. Treatment effects reported in the extant literature, as well as the factors that may strengthen or dampen these effects are reviewed. We find that social norm and incentive-based interventions mostly achieve small reductions in energy consumption, and that the effects of commitment-based interventions are essentially zero for the most part. Incentive effects on energy efficiency investments are mostly non-existent, safe for a few exceptions. One gap that we identify is the almost complete absence of field experiments leveraging social norms or commitment to promote energy efficiency investments. We discuss a broad range of (mostly under-researched) plausible moderators of the interventions’ effects. Crucially, a more careful attention to moderators in future research can highlight instances in which interventions can be effective, notwithstanding their modest or non-existent average treatment effects. Our review offers a starting point in this regard.